Penerapan Ajaran Tri Hita Karana Dalam Tradisi Baris Tengklong di Pura Tambang Badung Kelurahan Pemucutan Denpasar - Surya Andika, Putu; Sariani Binawati, Ni Wayan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Education is actually a process of inheriting a culture from one generation to the next. Education is defined as the process of changing the attitudes and behavior of a person or group of people in an effort to mature through teaching and training efforts. However, the world of education in Indonesia is not devoid of criticism and rebuke. In addition to the implementation of the education curriculum policy which is still complicated, the high cost of education to the poor quality of Indonesia is still the talk of all Indonesian citizens. But it cannot be denied that the development of digital technology also has a negative impact on the world of education. Excessive use of information technology has proven to have a negative impact on conceptual thinking skills. In response to the above, the author has an assumption that it can be overcome with the concept of Tri Hita Karana. The method used is qualitative research method, which is a type of research that examines and can describe complex and concrete social realities. The application of Tri Hita Karana teachings in the Baris Tengklong tradition at Badung Mine Temple, Pemucutan Village, West Denpasar is a cultural practice that illustrates the harmony and balance between three important aspects of Balinese life, namely human relations with God, human relations with each other, and human relations with nature. Thus, the application of the Tri Hita Karana teachings in the Baris Tengklong tradition at the Badung Mine Temple in Pemucutan Village, West Denpasar, is a clear example of how Balinese culture integrates spiritual, social, and ecological principles to create balance and harmony in their daily lives. This ceremony is a concrete manifestation of Balinese people's lives that pay great attention to harmony in relationships with God, fellow humans, and the surrounding nature. Overall, the application of Tri Hita Karana teachings in the Baris Tengklong tradition at Badung Mine Temple, Pemucutan Village, West Denpasar is a concrete example of how these teachings are still very relevant and alive in the daily lives of Balinese people. It is a manifestation of the way Balinese people try to maintain balance and harmony with nature, gods, and fellow humans in an effort to achieve happiness and prosperity together.